2020
DOI: 10.3390/microorganisms8020235
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ Possesses Anti-Microbial and Immunomodulatory Activity on a Chlamydia trachomatis Infection Model of Primary Human Synovial Fibroblasts

Abstract: Chlamydia trachomatis, an obligate intracellular pathogen, is the most common cause of bacterial sexually transmitted diseases, and it is potentially responsible for severe chronic sequelae, such as reactive arthritis. To date, details of the mechanisms by which Chlamydiae induce innate antimicrobial pathways in synovial fibroblasts, are not well characterized; therefore, herein, we investigated the effects of interferon (IFN)α, IFNβ, and IFNγ on the infection, and replication phases of the C. trachomatis deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…Although the basis for caspase-1 stimulation of chlamydial infection is not well defined [32] and remains poorly characterized in our human synovial cell model, we found that exposure of C. trachomatis-infected cells to IFN-γ may modulate the canonical inflammasome pathway by reducing the gene expression of caspase-1. These findings support our previous work on anti C. trachomatis activity of IFN-γ and yield novel insights into mechanisms by which this cytokine could interfere with its replication [11]. Previous studies have shown that caspase-1 can be upregulated by IFN-γ in distinct cell lines [33][34][35].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Although the basis for caspase-1 stimulation of chlamydial infection is not well defined [32] and remains poorly characterized in our human synovial cell model, we found that exposure of C. trachomatis-infected cells to IFN-γ may modulate the canonical inflammasome pathway by reducing the gene expression of caspase-1. These findings support our previous work on anti C. trachomatis activity of IFN-γ and yield novel insights into mechanisms by which this cytokine could interfere with its replication [11]. Previous studies have shown that caspase-1 can be upregulated by IFN-γ in distinct cell lines [33][34][35].…”
Section: Discussionsupporting
confidence: 89%
“…Caspase-1 activated IL-18 is also a potent inducer of IL-1β, IL-8, and interferon (IFN)γ [20,21], which has been demonstrated to play a key role in the clearance and protection against C. trachomatis by modulating a plethora of host cell signaling pathways [22,23]. Interestingly, in our recent study, the anti-chlamydial activity of IFN-γ has also been demonstrated in primary human synovial fibroblasts through the modulation of the hostcell innate immune responses, as evidenced by an increased expression of TLR2, 3 and 4, and IFN-related pathways, including GAS, STING, IRF9, ISG56, and GBP1 [11].…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations